Hierarchy Process Analysis as a Determination of the Optimization Strategy for UMKM Business Licensing at the DPMPTSP of Sampang Regency Based on Economic and Institutional Criteria - Alifia Azzahrah (Green Publisher Indonesia, 2026)
This study aims to determine the application of institutional economics concepts—particularly transaction costs, principal-agent relationships that may lead to moral hazards, and information asymmetry—in the UMKM business licensing process at the DPMPTSP of Sampang Regency, as well as to identify the results of the Analytic Hierarchy Process (Analytic Hierarchy Process or AHP) for prioritizing strategies to optimize UMKM business licensing at the DPMPTSP of Sampang Regency. This study employs a descriptive method with a case study design and a qualitative approach. Primary data were obtained from interviews and questionnaires distributed to informants selected via purposive sampling techniques. Internal obstacles to issuing the NIB through OSS RBA include server disruptions on the website and limited internet access. External obstacles involve bribery practices and business actors' limited understanding of digital technology. The study results indicate that micro- and small-scale business actors still incur transaction costs, such as indirect and opportunity costs; opportunistic behaviors and external moral hazards arise from bribery, procedural inconsistencies, and limited access to licensing urgency and regulations. AHP results identify priority strategies for optimizing business licensing: improving officer performance and business actors' understanding, as well as proactive initiative (